2021
DOI: 10.1016/j.jseint.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of nonoperative management of displaced olecranon fractures in medically unwell patients

Abstract: Background Surgical treatment of displaced olecranon fractures in the elderly has a high rate of complications, including wound breakdown and fixation failure. The purpose of this study was to assess the clinical, radiographic, and functional outcomes of nonsurgical management of displaced olecranon fractures in low-demand elderly and medically unwell patients. Methods A retrospective review of 28 patients with displaced closed olecranon fractures was performed with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…nonoperative management may be considered for both mayo type IIa and type IIB displaced olecranon fractures in select elderly patients, given the conflicting outcomes observed following the surgical management of these injuries. 15,16 there is now a growing body of evidence supporting the role of nonoperative treatment for displaced olecranon fractures in older patients with low functional demands (table III), 10,22,29,[104][105][106] where comorbidities, preinjury functional status, bone quality, and potential complications following surgery may affect the outcome. Knots buried on dorsal surface underneath anconeus nonoperative management routinely involves early active range of motion, with a cast or sling required for pain alone.…”
Section: Management: Nonoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…nonoperative management may be considered for both mayo type IIa and type IIB displaced olecranon fractures in select elderly patients, given the conflicting outcomes observed following the surgical management of these injuries. 15,16 there is now a growing body of evidence supporting the role of nonoperative treatment for displaced olecranon fractures in older patients with low functional demands (table III), 10,22,29,[104][105][106] where comorbidities, preinjury functional status, bone quality, and potential complications following surgery may affect the outcome. Knots buried on dorsal surface underneath anconeus nonoperative management routinely involves early active range of motion, with a cast or sling required for pain alone.…”
Section: Management: Nonoperative Managementmentioning
confidence: 99%
“…The authors reported that just over one-third of patients (n = 9; 35%) had a minor loss of extension strength and 22 (85%) developed a radiological nonunion, but with a high mean satisfaction score. More recently, Aibinder et al 105 similarly reported on 28 patients (mean age 79 years) treated nonoperatively with either a sling, an above-elbow cast, or an above-elbow splint. At a mean follow-up of 11 months, the mean elbow flexion arc was from 28° to 127°, and the majority of patients had regained active extension strength against gravity with no or minimal discomfort at the fracture site.…”
Section: Management: Nonoperative Managementmentioning
confidence: 99%
“…Nonoperative management or fragment excision with triceps advancement are generally reserved for low-demand elderly patients or those who would not otherwise tolerate an operation. 1,3,4…”
Section: Introductionmentioning
confidence: 99%
“…Nonoperative management or fragment excision with triceps advancement are generally reserved for low-demand elderly patients or those who would not otherwise tolerate an operation. 1,3,4 The goal of ORIF of olecranon fractures is to restore congruity at the articular surface, restore triceps function, and provide stable fixation sufficient to allow for early active range of motion (ROM). [1][2][3]5 Depending on the fracture pattern, different fixation techniques may be employed.…”
Section: Introductionmentioning
confidence: 99%